A Cross-sectional study: Head Injury in children of Karachi - Ahmed , Aftab; Syed Muhammad Mustahsan; Tariq, Fateeha; Abidi, Syed Muhammad Ali; Aslam, Muhammad Owais (International Journal of Endorsing Health Science Research, 2015)
A cross-sectional study was conducted to determine the prevalence, causes and outcome of head injury in children at Neurosurgery Department of Jinnah Postgraduate Medical Centre from 1st December, 2013 to 1st February, 2014. A total of 37 patients under the age of 12 years, presented with head injuries to the emergency department, were included in the study. A self-designed questionnaire was filled for these children after getting the oral consent from their parents. The questionnaire comprised a complete detail on the causes of head injury, clinical presentation on reaching the hospital, X-rays and Computed Tomography (CT) scans of the children and their reports. SPSS version 20 was utilized as an analytical tool. The mean age of patients was 6.93 years ± 3.02. Out of these 37 patients, 54.1% were males and 45.9% were females. Road traffic accidents accounted for most of cases (48.6%) with marked peak observed in boys as compared to the girls. Majority had a good Glasgow Coma Scale (GCS) score (43.2%) whereas a depressed fracture was found to be the dominant feature (21.6%) on X-rays. Additionally, 29.7% of children had intracranial hemorrhage while 32.4% also acquired other injuries. In total 29.7% were offered surgical intervention with majority (83.8%) landing in neurosurgical ward. As head injury in childhood is an important issue, keeping in view the lack of research in this field we need to properly highlight the burden of such injuries in childhood so that all the concerned governing authorities should take every possible step in preventing as well as managing this devastating health concern.